2016
DOI: 10.1073/pnas.1602379113
|View full text |Cite
|
Sign up to set email alerts
|

Derepression of hTERT gene expression promotes escape from oncogene-induced cellular senescence

Abstract: Oncogene-induced senescence (OIS) is a critical tumor-suppressing mechanism that restrains cancer progression at premalignant stages, in part by causing telomere dysfunction. Currently it is unknown whether this proliferative arrest presents a stable and therefore irreversible barrier to cancer progression. Here we demonstrate that cells frequently escape OIS induced by oncogenic H-Ras and B-Raf, after a prolonged period in the senescence arrested state. Cells that had escaped senescence displayed high oncogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
95
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(104 citation statements)
references
References 52 publications
9
95
0
Order By: Relevance
“…While normal fibroblasts treated with TGF‐β1 developed dysfunctional telomeres and upregulated α‐SMA expression in a time‐dependent manner, hTERT‐expressing fibroblasts did not develop TIF and showed diminished α‐SMA expression (Figure 3c,d and Supporting Information Figure S3e). Similarly, using human fibroblasts in which dysfunctional telomeres can be repaired using a doxycycline inducible hTERT expression system (Patel et al, 2016), we demonstrate that induction of hTERT expression in TGF‐β1 transdifferentiated myofibroblasts again reduced the levels of α‐SMA expressed in cells (Supporting Information Figure S3f). While the primary function of telomerase is to elongate telomeres and suppress formation of dysfunctional telomeres generated due to telomere shortening and ROS‐induced telomeric replication stress, (Boccardi et al, 2015; Patel et al, 2016), telomerase also possesses noncanonical functions that promote DNA repair and cell survival (Martinez & Blasco, 2011).…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…While normal fibroblasts treated with TGF‐β1 developed dysfunctional telomeres and upregulated α‐SMA expression in a time‐dependent manner, hTERT‐expressing fibroblasts did not develop TIF and showed diminished α‐SMA expression (Figure 3c,d and Supporting Information Figure S3e). Similarly, using human fibroblasts in which dysfunctional telomeres can be repaired using a doxycycline inducible hTERT expression system (Patel et al, 2016), we demonstrate that induction of hTERT expression in TGF‐β1 transdifferentiated myofibroblasts again reduced the levels of α‐SMA expressed in cells (Supporting Information Figure S3f). While the primary function of telomerase is to elongate telomeres and suppress formation of dysfunctional telomeres generated due to telomere shortening and ROS‐induced telomeric replication stress, (Boccardi et al, 2015; Patel et al, 2016), telomerase also possesses noncanonical functions that promote DNA repair and cell survival (Martinez & Blasco, 2011).…”
Section: Resultssupporting
confidence: 67%
“…Similarly, using human fibroblasts in which dysfunctional telomeres can be repaired using a doxycycline inducible hTERT expression system (Patel et al, 2016), we demonstrate that induction of hTERT expression in TGF‐β1 transdifferentiated myofibroblasts again reduced the levels of α‐SMA expressed in cells (Supporting Information Figure S3f). While the primary function of telomerase is to elongate telomeres and suppress formation of dysfunctional telomeres generated due to telomere shortening and ROS‐induced telomeric replication stress, (Boccardi et al, 2015; Patel et al, 2016), telomerase also possesses noncanonical functions that promote DNA repair and cell survival (Martinez & Blasco, 2011). To determine whether noncanonical functions of hTERT contribute to the suppression of myofibroblast transdifferentiation, we overexpressed in human BJ fibroblasts DN‐hTERT, a dominant defective mutant of hTERT that inactivates the catalytic activity of hTERT while leaving its noncanonical functions intact (Hahn et al, 1999).…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…However, it was recently reported that some OIS cells acquire chromatin changes that promote the expression of the human telomerase reverse transcriptase gene (hTERT) and, as a consequence, escape senescence [94]. This can have important consequences for tumor formation, as senescent cells share features of the cancer epigenome [35].…”
Section: Resultsmentioning
confidence: 99%